2011
DOI: 10.1111/j.1365-2133.2011.10230.x
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset inversa recessive dystrophic epidermolysis bullosa caused by glycine substitutions in collagen type VII

Abstract: Dystrophic epidermolysis bullosa (DEB) is a rare hereditary skin disorder caused by mutations in COL7A1, encoding collagen type VII.1 Clinical manifestations of COL7A1 mutations range from generalized skin blistering to mild localized blistering or nail dystrophy.2 The investigation of the molecular basis of DEB has revealed more than 540 different mutations that cannot entirely explain phenotypic variations (HGMD Professional 2010.3, https://portal.biobase-international. com/hgmd/). Inversa recessive DEB (RDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Up to now, more than 800 genetic variants of COL7A1 are related to DEB (http://www.col7a1-database.info) (Wertheim‐Tysarowska et al, 2012). Among these, almost all mutations are glycine substitutions located in triple helix domain (THD; Leverkus et al, 2011). The clinical phenotypes of DDEB are comparatively milder than that of RDEB.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, more than 800 genetic variants of COL7A1 are related to DEB (http://www.col7a1-database.info) (Wertheim‐Tysarowska et al, 2012). Among these, almost all mutations are glycine substitutions located in triple helix domain (THD; Leverkus et al, 2011). The clinical phenotypes of DDEB are comparatively milder than that of RDEB.…”
Section: Discussionmentioning
confidence: 99%
“…So far, more than 730 mutations on the COL7A1 gene have been revealed to be involved in DEB, most of which are glycine substitution mutations located at the triple helix domain [10]. It has been reported that approximately 75% of the DDEB mutations occur in exons 73–75 [11], while RDEB are caused by mutations on both alleles that result in either null alleles or out-of-frame mutations from insertions/deletions, single-base substitutions, and splice junction alterations [12][16].…”
Section: Discussionmentioning
confidence: 99%
“…Dystrophic epidermolysis bullosa is a clinically heterogeneous skin disease in the forms of dominant and recessive inheritance. [1][2][3][4] Dystrophic epidermolysis bullosa -1 which was identified by Gedde and Dahl for the first time in 1971. 2 DEB-I is a rarely observed form of epidermolysis bullosa starting immediately after birth or at early infancy characterized by blister formation and erosions in flexural areas, frequently affecting the mucous membranes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermolysis bullosa (EB) describes a group of genetic diseases with impaired dermo-epidermal integrity and blistering and erosions of skin and mucous membranes after minimal trauma. 1,2 Dystrophic EB represents a subgroup with dermolytic blistering and scarring. The recessive group contains four clinical subtypes: generalized mutilating, generalized nonmutilating, inversa, and localized.…”
Section: Introductionmentioning
confidence: 99%